2014
DOI: 10.1002/ccd.25596
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping of small diameter stents: An in vitro study

Abstract: Stainless-steel, coronary stents of a closed-cell design unzip at twice their nominal diameter without significant shortening when serially dilated. This study may encourage the implantation of small stents in infant blood vessels and aid in selection of appropriate stent type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
4
22
2
Order By: Relevance
“…In theory, this technique allows for a comprehensive interventional strategy for the treatment of PA stenosis decreasing the number of surgeries for CHD patients. The ex‐vivo fracture characteristics of a number of commercially available small diameter stents have been defined . Recent animal studies determined feasibility and histologic consequences of acute stent fracture in systemic and pulmonary arteries and small single center studies have demonstrated initial clinical efficacy and safety of intentional stent fracture within the pulmonary vasculature .…”
Section: Introductionmentioning
confidence: 99%
“…In theory, this technique allows for a comprehensive interventional strategy for the treatment of PA stenosis decreasing the number of surgeries for CHD patients. The ex‐vivo fracture characteristics of a number of commercially available small diameter stents have been defined . Recent animal studies determined feasibility and histologic consequences of acute stent fracture in systemic and pulmonary arteries and small single center studies have demonstrated initial clinical efficacy and safety of intentional stent fracture within the pulmonary vasculature .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested by some authors that an alternative strategy to the problem of complex anatomy in small patients is to implant smaller diameter stents, some of which are commercially available in shorter lengths, and subsequently longitudinally fracture, or “unzip,” the stents using high‐pressure balloon dilation once the stent has reached its maximal diameter and the patient is a larger size . There is not enough published data to truly compare the safety and efficacy of each approach.…”
Section: Discussionmentioning
confidence: 99%
“…There is not enough published data to truly compare the safety and efficacy of each approach. However, it is concerning that this strategy can unpredictably result in incomplete or disorganized stent fractures and refractory stenosis, particularly if multiple stents are used. Not enough is known about the reliability of consistent complete longitudinal fracture in most stent types or about the histologic changes and long‐term tissue integrity and growth in the vessel wall at the fracture site to recommend this strategy over ours.…”
Section: Discussionmentioning
confidence: 99%
“…13 They determined that stainless steel stents with a closed-cell design, which shortened minimally during dilation, were most amenable to intentional fracture. Clinical data in this area are limited.…”
Section: Previous and Related Datamentioning
confidence: 99%